Next generation inline minority carrier lifetime metrology on multicrystalline silicon bricks for PV - Schüler, Nadine; Mittelstraß, Dirk; Dornich, Kay; Niklas, Jürgen; Neuhaus, Holger (IEEE Xplore digital library, 2010)
In this paper the novel method MDP (microwave detected photoconductivity) [1-4] will be introduced to the field of contact less inline metrology at bricks. By the application of a widely advanced microwave detection technique, it is now possible to map minority carrier lifetime and photoconductivity simultaneously, with a so far unsurpassed combination of spatial resolution, sensitivity, and measurement speed. Beside these two parameters the iron concentration can be detected and analyzing the photoconductivity at steady state in comparison with the minority carrier lifetime, a lot of additional information can be derived. This paper will show first examples of minority carrier lifetime and photoconductivity maps, along with resistivity linescans and iron concentration maps of whole bricks measured inline. Furthermore simulations will be provided. Solving the transport equations for electrons and holes during the measurement at bricks, it can be proven that the measured effective lifetime deviates only lightly from the actual bulk lifetime. Furthermore it becomes clear that a steady state generation is more suited for brick measurements than non-steady state methods.